Usefulness of patient studies in learning family medicine at postgraduate level - S.N. Jaffri; G.J.O. Marincowitz; N.H.B. Malete (South African Family Practice)
Background: The Master's in Family Medicine (M Fam Med) is a postgraduate training programme in family medicine at Medunsa. M Fam Med students have to write patient studies as part of requirements to complete their degree. This research was undertaken to develop a deeper understanding of their perceptions about patient studies.